2007
DOI: 10.1074/jbc.m608358200
|View full text |Cite
|
Sign up to set email alerts
|

CD44-dependent Intracellular and Extracellular Catabolism of Hyaluronic Acid by Hyaluronidase-1 and -2

Abstract: Hyaluronic acid (HA) is a high molecular weight glycosaminoglycan involved in a wide variety of cellular functions. However, its turnover in living cells remains largely unknown. In this study, CD44, a receptor for HA, and hyaluronidase-1, -2, and -3 (Hyal-1, -2 and -3) were stably expressed in HEK 293 cells and the mechanism of HA catabolism was systematically investigated using fluorescein-labeled HA. CD44 was essential for HA degradation by both endogenous and exogenously expressed hyaluronidases. Hyal-1 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
267
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 285 publications
(302 citation statements)
references
References 41 publications
13
267
1
6
Order By: Relevance
“…It has been suggested that HA is catabolized in a CD44-dependent manner [13ϳ15]. Our recent observation also revealed that CD44 has critical roles in the intracellular and extracellular catabolism of HA mediated by hyaluronidase-1 (Hyal-1) and hyaluronidase-2 (Hyal-2), respectively [16]. In addition, it has been shown that the signaling functions of HA are mediated by CD44 [17].…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…It has been suggested that HA is catabolized in a CD44-dependent manner [13ϳ15]. Our recent observation also revealed that CD44 has critical roles in the intracellular and extracellular catabolism of HA mediated by hyaluronidase-1 (Hyal-1) and hyaluronidase-2 (Hyal-2), respectively [16]. In addition, it has been shown that the signaling functions of HA are mediated by CD44 [17].…”
Section: Introductionmentioning
confidence: 78%
“…The membrane fractions from a cell line stably expressing human CD44 in HEK293 (CD44/293) [16,18] was used to determine the inhibitory activity of 1 for CD44-HA binding. The dose-dependent inhibition of CD44-HA binding by 1 is shown in Fig.…”
Section: Biological Activitiesmentioning
confidence: 99%
See 3 more Smart Citations